The international small group tree planting program (TIST) Kenya - Masiga, Moses; Yankel, C.; Iberre, C. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Case study for the report "Institutional innovations in African smallholder carbon projects" available at http://hdl.handle.net/10568/21222